Type 2 diabetes remission: multidimensional pharmacological strategies and future perspectives - Liu, Yang; Gang, Xiaokun; Liu, Xinming; Jiang, Wei; Yang, Yuqi; Wang, Guixia (Frontiers in Endocrinology, 2025)
The high prevalence and severe complications of type 2 diabetes mellitus (T2DM) pose significant threats to public health systems worldwide. An in-depth understanding of T2DM pathophysiology has brought focused attention to pharmacological strategies for achieving disease remission. However, limited knowledge exists regarding their efficacy, patient stratification strategies, and long-term effects. By constructing an analytical framework integrating “mechanism-drug-strategies,” we explore mechanisms of action and clinical effects of multiple medications (insulin, metformin, sodium–glucose cotransporter-2 inhibitors, and glucagon-like peptide-1 [GLP-1] receptor agonists) for T2DM remission and analyze synergistic effects of combination therapies. Short-term intensive insulin therapy significantly improves β-cell function and insulin sensitivity, resulting in sustained glycemic remission in certain patients. Novel multi-target drugs (GLP-1/gastric inhibitory polypeptide dual agonists) demonstrate significant glycemic control and weight loss advantages. Non-antihyperglycemic drugs (vitamin D, sex hormones) demonstrate diabetes remission potential. Combined therapies (insulin with oral hypoglycemic agents, multitarget oral drug combinations) improve remission rates and prolong remission duration. This study systematically synthesized evidence on the multidimensional progress in pharmacological interventions for T2DM remission to support clinical practice and promote the transition of T2DM remission from a theoretical concept to individualized clinical application. Through an in-depth analysis of drug mechanisms of action and clinical research, new perspectives and strategies for optimizing treatment plans, improving diabetes remission rates, and reducing medication burdens, potentially providing important references for global T2DM management, are described. Future research focusing on long-acting combination strategies, predictive model construction, and translational medicine validation may cause a paradigm shift, from “glycemic control” to “disease remission.”